Pwp1 Is Required for the Differentiation Potential of Mouse Embryonic Stem Cells Through Regulating Stat3 Signaling. (March 2015) - Shen, Junwei; Jia, Wenwen; Yu, Yangyang; Chen, Jie; Cao, Xinkai; Du, Yanhua; Zhang, Xiaobai; Zhu, Songcheng; Chen, Wen; Xi, Jiajie; Wei, Tingyi; Wang, Guiying; et al.
Abstract Leukemia inhibitory factor/Stat3 signaling is critical for maintaining the self‐renewal and differentiation potential of mouse embryonic stem cells (mESCs). However, the upstream effectors of this pathway have not been clearly defined. Here, we show that periodic tryptophan protein 1 (Pwp1), a WD‐40 repeat‐containing protein associated with histone H4 modification, is required for the exit of mESCs from the pluripotent state into all lineages. Knockdown (KD) of Pwp1 does not affect mESC proliferation, self‐renewal, or apoptosis. However, KD of Pwp1 impairs the differentiation potential of mESCs both in vitro and in vivo. PWP1 chromatin immunoprecipitation‐seq results revealed that the PWP1‐occupied regions were marked with significant levels of H4K20me3. Moreover, Pwp1 binds to sites in the upstream region of Stat3. KD of Pwp1 decreases the level of H4K20me3 in the upstream region of Stat3 gene and upregulates the expression of Stat3. Furthermore, Pwp1 KD mESCs recover their differentiation potential through suppressing the expression of Stat3 or inhibiting the tyrosine phosphorylation of STAT3. Together, our results suggest that Pwp1 plays important roles in the differentiation potential of mESCs. Stem Cells2015;33:661–673